Bottle milk feeding and its association with food group consumption, growth and socio‐demographic characteristics in Chinese young children. Issue 3 (26th July 2016) - Yeung, Suey; Chan, Ruth; Li, Liz; Leung, Shirley; Woo, Jean
Abstract: It is recommended that infants from the age of 12 months should be weaned from bottles. However, an overwhelming proportion of young children were still using bottle after the recommended age of bottle‐weaning. This cross‐sectional study examined the association between utensils for milk drinking and food group consumption, growth and socio‐demographic characteristics among young children. Data from the Survey of Infant and Young Child Feeding in Hong Kong were analyzed for 649 children aged 18–48 months old. Dietary outcomes were obtained via 3‐day dietary records, while utensils for milk drinking and socio‐demographic characteristics were collected from a self‐developed questionnaire. Length/height and weight of the children were measured by the nurses. Results showed that daily consumption of formula milk was significantly greater among bottle users or bottle plus cup users than non‐bottle users ( p < 0.05). Exclusive bottle users had significantly lower intakes of meat and meat alternatives than bottle plus cup users for the 18 to 24‐month group ( p = 0.001) and lower intakes of fruits than non‐bottle users in the 48‐month group ( p = 0.015). BMI z ‐score was significantly higher for exclusive bottle users than non‐bottle users, even after adjusting for socio‐economic factors and child's age ( p = 0.006). The results showed that the milk drinking utensil was associated with the amount of formula milk and food group consumption as well as BMI z ‐score. There is a need to actively discourage prolonged bottle use in order to help young children develop good dietary habits. © 2016 John Wiley & Sons Ltd